EXPERIENCES IN THE USE OF ARTILLERY IN THE ARMY OF AMIR TEMUR - Tukhtamurodov Akmal Akbaraliyevich (Modern American Journals, 2025)
This article describes the experiences of using artillery in the armies of Amir Temur. The contribution to the development of artillery during the period of Amir Temur, the fundamentals of Amir Temur’s martial art and management are discussed. There are examples of how the tactical methods used by our national artillery are based the use of artillery during time Amir Temur.